52 Endothelial progenitor cell responses to hypoxia: time-course dependent changes in Akt signalling and gene expression. Issue 20 (23rd September 2011) - Hookham, M B; Ali, I H A; McKenzie, R A; Loughrey, P B; O'Neill, C L; Medina, R J; O'Doherty, M; Stitt, A W; Brazil, D P
Abstract : The aim of this work was to examine endothelial progenitor cells (EPCs) and their potential role as a cell based autologous therapy to revascularise the ischaemic tissue of the diabetic retina. Our group have isolated and characterised a distinctive human blood derived EPC with high proliferative capacity known as outgrowth endothelial cells (OECs). To mimic low O2 concentrations in the ischaemic retina, we have exposed OECs to 1% O2 for varying times. Hypoxia induces reduced cell proliferation, cell senescence and increased cell size in OECs. Changes in Akt activity, a key regulator of cell proliferation were noted after 30 min exposure to hypoxia which then returned to basal levels by 1 h. Hypoxia also induced considerable alterations in the phosphorylation status of several proteins involved in mTOR signalling, a crucial regulator of cell size. Acute exposure (30 min) to 1% O2 triggered p70S6 K phosphorylation in OECs. In contrast chronic exposure to hypoxia resulted in a considerable decrease in p70S6 K which correlated closely with an increase in both AMPK and Raptor phosphorylation. We have also identified that BMP pathway activation is a feature of OEC responses to hypoxia, with rapid induction of Smad1/5/8 phosphorylation observed in these cells within 60 min of hypoxia. The effect of recombinant BMPs on OEC tube formation and other angiogenic markers is currently being examined. These data provide novel insights into OEC responses in the hypoxic/ischaemic milieu, and have important implications for micro and macrovascular damage seen in diabetes.